Heterosis and combining ability for yield and anthracnose disease resistance in chilli hybrids (Capsicum spp) - Herath, Herath Mudiyanselage Shalika Nadeeshani (2022)
Chilli (Capsicum species) is an important spice and vegetable crop in Malaysia. In 2019, the self-sufficiency ratio for chilli was recorded at 30.8% indicating the importance of increasing chilli production in the country. Chilli production in Malaysia is hampered by many diseases. One of the major diseases in chilli is anthracnose. Anthracnose disease caused by Colletotrichum species is a devastating fungal disease that resulted in huge yield losses in chilli cultivation. Thus, this study was conducted to develop high yielding anthracnose disease-resistant chilli hybrids. The study is composed of four parts. In the first part of the study, 32 inbred lines were evaluated for yield and yield component traits under randomized complete block design (RCBD) with three replicates to assess the genetic variability among inbred lines and identify high yielding parents for F1 hybrid production. Highly significant differences were observed among inbred lines for yield and yield-related traits indicating the high genetic variability. Inbred line, MICH PL CC 2018/33 was recorded the highest yield per plant followed by MICH PL 21. The trait, number of fruits per plant recorded the highest phenotypic coefficient of variance (PCV) and genotypic coefficient of variance (GCV) (78.01% and 53.97, respectively) followed by the yield per plant (53.09% and 34.29% respectively) confirming high genetic variability among inbred lines for these traits. In the second part, 32 inbred lines were included to evaluate the anthracnose disease severity. Four inbred lines, MICH PL CA 2018/3, MICH PL CA 2018/20, MICH PL CA 2018/21, MICH PL 35 and MICH PL CC 2018/17 were identified as resistant lines for anthracnose disease caused by C. truncatum. In the third part of the study, combining ability among inbred lines and the heterosis exhibited by the chilli hybrids for yield and anthracnose disease resistance were studied. The hybrids were obtained by crossing seven inbred lines that were selected based on the first and second parts of the study. A total of 23 genotypes consisting of 14 successful single cross hybrids, seven parents and two check varieties were evaluated in two environments for their yield and yield component traits. Simultaneously, anthracnose disease severity assessment was done for the chilli hybrids, parents and check varieties as the fourth part of the study. Under the combined data analysis over two environments, significant general combining ability (GCA) was exhibited in female parents for the traits, number of fruits per plant and fruit length. The traits, number of fruits per plant, number of days to fruit maturity, stem diameter, anthracnose disease severity as green mature fruits and red ripened fruits in male parents recorded significant GCA. This indicated the high influence of additive genetic effect for these traits. Specific combining ability (SCA) variances were significant for traits, yield, number of fruits per plant, fruit length, fruit diameter, pericarp thickness, average fruit weight, number of days to first flowering, number of days to maturity, plant height, canopy width and number of primary branches indicating preponderance of non-additive genetic effect in the inheritance of these studied traits. Out of 14 produced hybrids,10 hybrids exhibited resistance to anthracnose disease at green mature fruit stage and red ripe fruit stage with 5 of them, H1, H3, H4, H6 and H8 showed comparable yield data with imported commercial hybrid variety SJ2-46. Hybrids, H8, H3, H4 and H6 exhibited 22.5%, 12.07%, 6.5%, 5.2% higher yield respectively when compared to local commercial open pollinated variety Kulai 907. Further, these five hybrids with high mean performance recorded high mid parent heterosis (MPH) and better parent heterosis (BPH) for yield and anthracnose disease severity indicating the availability of hybrid vigour for commercial production of high yielding hybrids with anthracnose resistance. Among the parental inbred lines, male parents, MICH PL CC 2018/3 and MICH PL CA 2018/21 were identified as good general combiners for the yield. Good general combiners for anthracnose disease resistance were MICH PLCC 2018/3, MICH PL CA 2018/20, MICH PL CA 2018/21 and MICH PL 35. Hybrids, H4, H10, H2 and H7 recorded significant positive SCA for yield. None of the hybrids was a good specific combiner for anthracnose disease severity. Anthracnose disease resistance in parents and hybrids were further confirmed using the molecular markers linked to anthracnose disease resistance gene. This was carried out using previously identified SSR and STS markers. The screening of the hybrids revealed that all hybrids which were identified as resistant by the disease severity test carry the resistant gene for anthracnose disease. In this study, it was proved that the yield and most of the yield-related traits are highly controlled by the non-additive genetic effect that could be exploited during heterosis breeding. Highly significant heterosis values for yield and most of the yield-related traits indicated the availability of hybrid vigour in chilli for hybrid production in commercial level. Comparatively high yield and anthracnose disease resistance against C. truncatum, the chilli hybrids H1, H3, H4, H6 and H8 could be promising candidates to include in multi-locational trials before releasing for commercial cultivation in Malaysia.